Strategic Leadership Transformation through the Integration of Artificial Intelligence in Organizational Decision Systems: A Comparative Study on Technology Companies in Indonesia - Vika Fransisca; Wahyu Eko Saputro (PT. Publikasiku Academic Solution, 2026)
The development of Artificial Intelligence (AI) technology has driven transformation in various aspects of the organization, including in strategic leadership roles and patterns. In the midst of the digital acceleration that has occurred in Indonesia's technology sector, organizational leaders are required to be able to integrate AI in the strategic decision-making process to remain adaptive and competitive. This study aims to analyze how strategic leadership transformation occurs through AI integration, as well as compare its approaches across five technology companies in Indonesia. The approach used is a mixed methods with a sequential explanatory design, involving 100 quantitative respondents and 10 qualitative informants from the managerial and executive levels. The results show that the integration of AI in strategic decisions is still limited to a small percentage of companies and is highly dependent on digital literacy, leadership style, and organizational cultural readiness. Leaders who are adaptive to technology demonstrate the ability to optimize AI as a strategic partner, not just a technical tool. In addition, organizations with open structures and collaborative cultures are experiencing data-driven leadership transformations faster. The research also produced a conceptual model that illustrates the linkages between leadership, AI, and organizational readiness as a framework for sustainable digital transformation. The findings are expected to be a reference both practically and theoretically for the development of strategic leadership in the era of artificial intelligence.